2004
DOI: 10.1136/sti.2003.006395
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chlamydia trachomatis serovar distribution changes in the Netherlands (1986-2002)

Abstract: If you have a burning desire to respond to a paper published in Sex Transm Infect, why not make use of our ''eLetters'' option? Log on to the STI website (www.stijournal. com), find the paper that interests you, click on [Abstract], or response by clicking on ''eLetters submit a response''. Providing your letter isn't libellous or obscene, it will be posted within seven days. You can view recent eLetters by clicking on ''read eLetters'' on our homepage. As before, the editors will decided whether to publish it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
3
13
1
Order By: Relevance
“…The possible association between demographics, sexual behavioural data, rectal symptoms, clinical manifestations 7), and had had sex in the last 6 months with more partners (p = 0.009; OR: 2.0; 95% CI: 1.2 to 3.5). However, these serovar L2 positive patients said they had used condoms in anal sexual contacts more often (p = 0.027; OR: 3.5; 95% CI: 1.2 to 10.6).…”
Section: Univariable and Multivariable Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible association between demographics, sexual behavioural data, rectal symptoms, clinical manifestations 7), and had had sex in the last 6 months with more partners (p = 0.009; OR: 2.0; 95% CI: 1.2 to 3.5). However, these serovar L2 positive patients said they had used condoms in anal sexual contacts more often (p = 0.027; OR: 3.5; 95% CI: 1.2 to 10.6).…”
Section: Univariable and Multivariable Analysesmentioning
confidence: 99%
“…Differences in ethnic composition between these two large Dutch cities was considered a possible explanation. 7 Compared to urogenital infections, little is known of serovar distribution in rectal chlamydial infection. 2 4 8 9 Serovars D-K have not consistently been investigated together with C trachomatis serovar L2.…”
mentioning
confidence: 99%
“…10 Ultimately, less shedding would reduce the number of ifu available to sustain infection, which might contribute to a shorter and less invasive infection, as seen in the mouse model, and a reduced level of transmission among humans, which would explain the well documented difference in the prevalence of infection with these serovars in human populations from around the world. [3][4][5][6][7][8][9] ''The ability to produce large numbers of infectious units rapidly probably contributes to the ability of C muridarum to ascend the genital tract and ultimately deliver an infectious challenge to the upper genital tract within the first seven days of infection, which results in the severe pathology seen during C muridarum infection''…”
Section: *Confluentmentioning
confidence: 99%
“…2 However, surveys of genital isolates from around the world have consistently shown that certain serovars occur more frequently than others, and that over time this pattern has remained constant. [3][4][5][6][7][8][9] Specifically, in large surveys in the USA and Europe, serovars D and E account for approximately 50% of genital C trachomatis isolates, whereas serovar H is isolated from only 1-3% of culture confirmed infections. In addition, differences in the level of shedding among serovars have been noted in clinical specimens that roughly correlated with serovar prevalence.…”
mentioning
confidence: 99%
“…From each female two cervical swabs were taken. One was assessed for the presence of C. trachomatis DNA as described previously (14). A second cervical swab was placed in 0.4 M sucrose phosphate buffer (4SP) medium and used for C. trachomatis culture as well as DNA extraction.…”
mentioning
confidence: 99%